2011
DOI: 10.1002/hbm.21298
|View full text |Cite
|
Sign up to set email alerts
|

The mentalizing network orchestrates the impact of parochial altruism on social norm enforcement

Abstract: Parochial altruism-a preference for altruistic behavior towards ingroup members and mistrust or hostility towards outgroup members-is a pervasive feature in human society and strongly shapes the enforcement of social norms. Since the uniqueness of human society critically depends on the enforcement of norms, the understanding of the neural circuitry of the impact of parochial altruism on social norm enforcement is key, but unexplored. To fill this gap, we measured brain activity with functional magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
152
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 78 publications
11
152
1
1
Order By: Relevance
“…The same argument holds for the observed activation in the dorsomedial prefrontal cortex (dMPFC, BA 10; Supplementary Fig. 2b), which has been implicated in mind-reading tasks in numerous studies 12,38,39 . Subjects in the right and left TMS group showed no differential activation in these areas, suggesting that this brain region is equally capable of processing the reading of intentions behind unfair offers in both treatment groups.…”
Section: Neural Effects In the Stimulated Brain Regionssupporting
confidence: 63%
See 1 more Smart Citation
“…The same argument holds for the observed activation in the dorsomedial prefrontal cortex (dMPFC, BA 10; Supplementary Fig. 2b), which has been implicated in mind-reading tasks in numerous studies 12,38,39 . Subjects in the right and left TMS group showed no differential activation in these areas, suggesting that this brain region is equally capable of processing the reading of intentions behind unfair offers in both treatment groups.…”
Section: Neural Effects In the Stimulated Brain Regionssupporting
confidence: 63%
“…Studies on such subjects also have limited opportunities for experimental manipulations, and there is the possibility of functional reorganization after brain lesions, rendering the interpretation of behavioral differences in terms of neural characteristics difficult. To overcome these limits, recent studies used brain imaging methods [7][8][9][10][11][12][13][14][15] and brain stimulation methods [16][17][18] to investigate the neural mechanisms behind normative decisions.…”
mentioning
confidence: 99%
“…The (un) fairness of choices resulting in outcome distributions is therefore encoded in neural structures that overlap with those often presumed to encode anticipated values of non-social choices (which is in accordance with the extended common currency schema). However, in close similarity to the effects of vicarious reward experience (discussed above), fairness-related neural responses and the associated behaviour can strongly depend on contextual factors, such as the proposer's intentions 92 , the relation of a specific offer's distribution to the average in a series of offers 93 or whether the opponent belongs to the player's social group or a rival group 96 . This contradicts a direct, automatic mapping of the objective 'fairness' of others' decisions to neural responses in the reward system and raises questions about the origins of these value-related responses.…”
Section: Neural Valuation Of Normative Social Principlesmentioning
confidence: 97%
“…This contradicts a direct, automatic mapping of the objective 'fairness' of others' decisions to neural responses in the reward system and raises questions about the origins of these value-related responses. One possible mechanism by which social principles may influence value-coding regions is through functional connectivity with areas involved in social cognition (such as the TPJ and dmPFC 96 ), as has been observed for basic social reward experience 38 and for altruistic 45 and vicarious 69 choices. Valuation-related neural brain structures may also be implicated in abstract social decisions that do not involve any personal gains or losses for the participant.…”
Section: Neural Valuation Of Normative Social Principlesmentioning
confidence: 99%
“…People were more likely to cooperate with members of their own group, and, as in Bernhard et al, third parties were more likely to punish when an in-group member had been the victim of defection, showing that this finding holds across different economic contexts and group manipulations. Still other studies have shown that third parties are particularly protective of in-group victims when norm violations are committed by out-group members [22,49,50].…”
Section: Group Bias In Sharing Behaviourmentioning
confidence: 97%